PENGARUH PEMBIAYAAN PERMODALAN NASIONAL MADANI TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN SUMBAWA - Insani, Maya; Sucihati, Roos Nana (Pusat Riset dan Publikasi, 2024)
This study aims to determine the effect of PT. PNM financing on the income of micro, small and medium enterprises in Sumbawa District. This study aims to determine the role of fishermen's wives in increasing family income. The type of this study was associative which aims to examine the effect of PT. PNM financing (X) on MSME income (Y). The type of data used in this study is quantitative data collected by researchers directly from research respondents using a research instrument in the form of a questionnaire. The number of samples that will be used as respondents in this study is 30 financing customers of PT. PNM in Sumbawa District which is determined using a non-probability sampling technique with a saturated sampling method. All data that has been collected was processed using the SPSS program to be analyzed and interpreted using simple linear regression analysis techniques, partial hypothesis testing (t test), and coefficient of determination testing (R2). The results of this study showed that PT. PNM financing had a positive and significant effect on MSME income in Sumbawa District. The degree of effect of PT. PNM financing variables on MSME income in Sumbawa District was 77%, while the remaining of 23% was effected by other variables outside this research model, such as digital marketing strategies, product innovation, and business capital.